AAC Clinical Education: Measuring Outcomes With Single Subject Designs. - Hyppa-Martin, Jolene (Perspectives of the ASHA Special Interest Groups, 2016)
Single subject experimental designs are a clinical tool that enable speech-language pathologists to make low-inference, data-driven intervention decisions and can be particularly useful when treating heterogeneous clinical populations for which there is limited directly applicable extant scientific evidence. Single-subject experimental designs are also useful in supporting the development of clinical expertise for speech-language pathologists and graduate students. This article provides a basic overview of the role of single-subject experimental designs in augmentative and alternative communication clinical education and the potential contributions that the application of these designs can make to the field of augmentative and alternative communication.